PENENTUAN RUTE TERBAIK PENDISTRIBUSIAN DENGAN METODE ANT COLONY OPTIMIZATION (STUDI KASUS PERUSAHAAN JASA PERGUDANGAN SPAREPART JAWA BARAT) - Annisa Indah Pratiwi; Sri Sustariyah; Akda Zahrotul Wathoni; Sobar Pazri; Dimas Cheli Ahsanunadia (Lembaga Penelitian dan Pengabdian pada Masyarakat, Universitas Buana Perjuangan Karawang, 2023)
This study aims to determine the best route for spare part product distribution. This research was conducted in one of the companies engaged in the production of spare parts, where in the company there is a Logistics department that functions to handle the product distribution process. In the process of distributing goods, costs are required. In addition, the trucks used in the process of distributing goods to each distributor go through different routes, so this research also aims to determine the best route based on the distance between locations. In order to obtain the best route, this research offers a solution using the Ant Colony Optimization (ACO) method by determining the route to be taken by the truck. The best route selection using the ACO algorithm uses the Traveling Salesman Problem (TSP) where one location point can only be made one visit. the best route results while the first cycle results are depots located in the area in the area of the best route V0-V4-V6-V2-V5-V7-V1-V8-V3-V0. That is the depot located in the Karawang area (V0) to MPP (V4), then to DAS (V6), then to KKI (V2), then to TBB (V5), then to MTN (V7), then to DYH (V1), then to MMH (V8), then to MSS (V3), and back to the depot (V0). The route covers a distance of 83 km. The route covers a distance of 255.5 km.Keywords: Ant Colony Optimization (ACO); Goods Distribution; Best Route